A PRESENÇA DE PROFISSIONAIS HOMENS NOS ANOS INICIAIS DO ENSINO FUNDAMENTAL: UM ESTUDO DE REVISÃO - Luis Fernando Martins Lopes (2023)
This dissertation – linked to the Postgraduate Program in Education at the Federal University of Mato Grosso do Sul (UFMS), Três Lagoas campus, and the research line “Teacher Training and Public Policies” – aims to study the presence of male teaching professionals in the early years of elementary school. For this purpose, the historical retrospective of the teaching profession will be presented, from its beginning, by the Jesuits, in the period of colonization, passing through all the political and social advents until the most recent data from the 21st century, which demonstrate a new presence of the male teacher in the early years of the elementary School. This proves to be a field of debate that will make it possible to highlight gender relations with a focus on masculinities and their constitution as a category of discussions and reflections, relating masculinities and femininities with the construction of being a teacher, thus seeking to use some authors who work on the theme, discuss the gender category associated with male teaching in the early years of elementary school, as well as masculinities when they enter this predominantly female space. To this end, the literature and scientific productions on masculinities and femininities in the early years of elementary school in the period 2011-2021 were revisited, articulating their research with the theme of the research presented, which in particular proved to be very scarce and limited, even though used different types of descriptors and search engines. The methodology used was a qualitative-quantitative approach, developed through the state of knowledge review study method to obtain theoretical material about the research. For understanding, data analysis and research forwarding, the study will have as references Ribeiro (2015), Caldas (2022), Scott (1992), Albuquerque Junior (2013), Vianna (2002), among other authors. In the end, the importance of discussing and thinking about the school environment as a place of gender equality, an environment for reviewing models of masculinity and femininity is exposed, especially when the masculine enters a space culturally constructed for the feminine, and can It is clear that there are still very few productions and postgraduate programs that articulate this type of theme, and we highlight the importance of research relating the presence of male professionals in the early years of primary education and discussions of gender – masculinity and femininities – related to same. Keywords: teaching profession; gender; masculinities.